ANALISA DAN INVESTIGASI LONGSORAN JEMBATAN TAMBAKBOYO PADA RUAS JALAN LINGKAR AMBARAWA - Rangga Aditya Pratama; Moga Narayudha; Siti Hardiyati (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Ambarawa is a small town in Central Java. The location is between the two major cities of Semarang and Yogyakarta. In the development of an increase in the density of traffic on the road Theater - MGR Soegijaapranata Ambarawa traffic density is due to the market Ambarawa have very solid activity around it and the narrowing of the road in front of the market. Therefore the construction of the ring road Ambarawa done. In the process of the construction of the ring road is a problem with the bridge construction Tambakboyo. The problem is the soil avalanche oprit pile on one side of the abutment. To address the problems with the structure of the solution taken Millipedes. The solution was taken because the original soil conditions where there is very unstable old former underground streams that support native land oprit heap. Oprit caused landslides on a sloping abutments, so it needs to be jacked back into position. The slope is not going to happen because the abutment unstable. To handle oprit While, based on the analysis and calculations, selected spoon piles with a diameter of 45 cm in the construction of the bridge 120 meters long millipede. Spoon piles Depth varies from 15 meters to 19 meters. To bind each pile pilecap are associated with beams. With the improvement in oprit expected to provide stability for the abutment and landslides again.